Marrons, colons, contrebandiers. Réseaux transversaux et configuration métisse sur la côte caraïbe colombienne (Dibulla) - Anne-Marie Losonczy (Journal de la Société des Américanistes)
Marroons, settlers, smugglers. Multipolar networks and mestizo configuration on the Colombian Caribbean coast (Dibulla). The social, territorial and religious organization of the Afro-American groups in the Dibulla area (Caribbean coast of Colombia) does not pertain to the model of isolated marroon societies, nor to the currently prevalent model of ethnicity mixed with religious neo-traditionalism rooted in africanity, nor to the deterritorialized forms of interactive identity found in urban settings. Their organization consists of multipolar networks of kindreds, articulated by rivalry and factionalism, the territorial basis of which is both matrifocal and religious, through localized cults to the saints and the dead. Their regime of memory and historicity, as well as their socio-political organization which overrides ethnic, regional and national borders, make this society a remarkable illustration of a kind of cross-border sociability, without community and definable collective identity, rarely studied by anthropologists. This form of society may be a distinctive facet of Caribbean cultures.